Radial Basis Function Autoregressive With Exogenous Based Model Predictive Controller For Waste To Energy Steam Boiler In Thermal Power Plants - Mehret, Getahun (ASTU, 2023)
Electrical Energy Is A Necessary Requirement In Our Common Daily Life As A Way Of Reconstructing Human Development To Financial Productivity. Renewable Energy Beginnings Are Substitutes To Increase Energetic Strength And Productivity, But They Need A Direct Control Structure To Receive Optimum Power Product. It Is New-Era Science Used To Produce Electricity From Household Waste, That Is Used To Decrease The Need For Landfills For Waste And Preserve The Use Of More Priceless Fuels, Thereby Protecting Raw Materials. A Boiler Turbine Generator Is An Energy Conversion Device That Is Commonly Used In Thermal Power Plants. The Boiler Unit Is One Of The Major Components In A Power Plant Which Is Used To Store Water And Collect The Steam By Heating The Water Of Tubes In The Tuber. The Control Mechanism Of Steam Boiler In Reppie Waste-To-Energy (Wte) Power Plant, Which Is Found In Ethiopia, Currently Uses Programmable Logic Controller (PLC). However PLC Is Logic Based Control And It Is Based On The Current Measurement Of The System Which Cannot Predict The Future Condition Of The System And It Cannot Handle The Constraints Inaddition Plcs Have Limitations In Their Ability To Capture The Nonlinear Behavior Of The System. This Thesis Considers Controlling The Drum Leve, Temperature And Pressure Of Waste To-Energy Thermal Power Plant Boilers Based On The Measured Input-Output Data Gather From Reppie Waste-To-Energy Plant. The Model Is Obtained Using System Identification Techniques Suchas Radial Basis Function Autoregressive With Exogenous Input (RBF-ARX) Model Then Applymodel Predictive Controller, In Which The Performance Is Compaired With (Linear Quadraticregulator) LQR. From The Result The LQR Has Around 5.99 Second But MPC Has Small Settling0.3955 Time For Temperature Also For Pressure The MPC Has Around 0.6678 Second And LQR Has12.507 Second Settling Time Lastly MPC Has 0.0195 Rise Time But LQR Has Very Large Rise Timetime To Regulate The Drum Level MPC Has 0.5223settling Time And LQR Has 8.302 Settling Time.Due To The Analysis The Proposed Controller MPC Has Better Performance For Setpoint Trackingthan LQR. The System Was Implemented Using MATLAB/Simulink.
Keywords: Thermal Power Plant, Mpc, Pid, Arx, Rbf, Matlab, System Identification.